Preparation method of LaB6 and Cr2Nb synergistically reinforced copper-based composite material

By introducing the LaB6 ceramic phase into the CuCrNb alloy, the problem of degradation of CuCrNb alloy at high temperatures is solved by mechanical ball milling and additive manufacturing combined with aging heat treatment, and the high temperature stability and conductive properties of the copper-based composite material are significantly improved.

CN119159099APending Publication Date: 2024-12-20XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411672092.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The high-strength and high-conductivity performance of CuCrNb alloys deteriorates rapidly during service in high-temperature cycles, and the solid solubility of nano-size Cr2Nb leads to a decrease in material strength and conductivity, which requires improvement of its thermal stability performance.

Method used

LaB6 powder and CuCrNb powder were mixed by mechanical ball mill to prepare CuCrNb composite powder coated by LaB6. LaB6 and Cr2Nb collaboratively reinforced copper-based composite materials were obtained through additive manufacturing and aging heat treatment, and high-temperature-resistant nanoceramic phase LaB6 was introduced to improve the material. high temperature stability.

Benefits of technology

By introducing the LaB6 ceramic phase, the high temperature stability and conductivity of the copper-based composite material are significantly improved, and the high strength and conductivity are maintained, solving the problem of the degradation of CuCrNb alloy at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159099A_ABST
    Figure CN119159099A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a LaB6 and Cr2Nb synergistically reinforced copper-based composite material. The method comprises the following steps: 1, carrying out ball milling and mixing on LaB6 powder and CuCrNb powder to obtain LaB6-coated CuCrNb composite powder; secondly, a formed part is obtained through additive manufacturing; and thirdly, aging heat treatment is conducted on the formed part, and the LaB6 and Cr2Nb synergistically-reinforced copper-based composite material is obtained. The additive manufacturing method is adopted, the high-temperature-resistant nano ceramic reinforced phase LaB6 is introduced into the CuCrNb alloy, aging heat treatment is combined for performance regulation and control, the LaB6 and Cr2Nb synergistic reinforced copper-based composite material is obtained, the high-temperature stability of the copper-based composite material is improved, the copper-based composite material has the comprehensive performance of high strength and high conductivity, and the copper-based composite material is suitable for the fields of aviation, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material additive manufacturing, and in particular to a method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material. Background Art

[0002] CuCrNb alloy is a high-strength, high-conductivity, high-thermal-conductivity, and heat-resistant copper alloy. It is prepared as the lining of the combustion chamber and used in the liquid oxygen, liquid hydrogen, and liquid oxygen-methane engines of spacecraft. The engine combustion chamber lining material needs to withstand harsh service conditions such as high temperature, impact, oxidation, and high temperature difference load cycles. NASA used a combination of aerosolization and additive manufacturing (3D printing) to prepare the CuCrNb (GRCop) alloy engine combustion chamber lining. The reason why this lining can cope with extreme working conditions is that the multi-scale Laves phase Cr2Nb plays a key strengthening role. Under high temperature and high stress service conditions, the multi-scale Cr2Nb hinders the grain boundary migration and avoids the softening of the material caused by the recrystallization growth of the 3D printed refined grains at high temperature, while the nano-sized Cr2Nb inside the grain plays the role of pinning dislocations to strengthen the matrix. In addition, in the Cr-rich CuCrNb alloy, the nano-scale Cr precipitated by aging can also strengthen the matrix. Studies have shown that CuCrNb alloy still has a strength of more than 100 MPa under cyclic service at 600°C, but it is still significantly lower than the strength of more than 600 MPa at room temperature.

[0003] According to relevant research, nano-sized Cr precipitates in Cr-rich CuCrNb alloys tend to grow at high temperatures, resulting in a decrease in strengthening. In addition, high-content Cr2Nb tends to agglomerate in the primary stage to form larger precipitates, which affects the material's strength, plasticity and heat resistance. It can be seen from the phase diagram that at high temperatures (above 800°C), Cr2Nb still has a certain solid solubility in the copper matrix, and the solid solution of some nano-sized Cr2Nb will also cause a sharp drop in material strength and reduce its electrical conductivity. Therefore, other methods are needed to further improve the thermal stability of the CuCrNb alloy.

[0004] Adding ceramic second phases to the Cu matrix to prepare composite materials has attracted much attention from researchers, such as Al2O3, TiB2, LaB6, Y2O3, WC, etc. The ceramic phase has extremely high melting point and strength, and has basically no solid solubility in the copper matrix. Nano-ceramic phase dispersion-enhanced copper-based composite materials can show excellent material structure thermal stability, as well as high strength and high conductivity in a wide temperature range. Selecting a suitable ceramic phase and using a matching preparation process to obtain a dispersed and non-segregated composite material is expected to further improve the thermal stability of the CuCrNb alloy. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a preparation method of LaB6 and Cr2Nb synergistically reinforced copper-based composite materials in view of the deficiencies of the above-mentioned prior art. The method prepares a CuCrNb composite powder wrapped with LaB6 by mechanically ball-milling LaB6 powder and CuCrNb powder, obtains a molded part by additive manufacturing, and then combines aging heat treatment to perform performance regulation to obtain a LaB6 and Cr2Nb synergistically reinforced copper-based composite material. By introducing a high-temperature resistant nano-ceramic reinforcement phase LaB6 into the CuCrNb alloy, the high-temperature stability of the copper-based composite material is improved, so that it has the comprehensive performance of high strength and high conductivity, and solves the problem that the high-strength and high-conductivity performance of the CuCrNb alloy rapidly deteriorates during high-temperature cyclic service.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a preparation method of LaB6 and Cr2Nb synergistically reinforced copper-based composite material, characterized in that the method comprises the following steps: Step 1: ball-milling LaB6 powder and CuCrNb powder to obtain CuCrNb composite powder coated with LaB6; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 to perform additive manufacturing to obtain a molded part; Step three: performing aging heat treatment on the molded part obtained in step three to obtain a LaB6 and Cr2Nb synergistically reinforced copper-based composite material.

[0007] The above-mentioned method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material is characterized in that the CuCrNb powder in step one is a CuCrNb spherical alloy powder prepared by a gas atomization method or a CuCrNb composite powder prepared by a mechanical alloying method, and the particle size is less than 50μm.

[0008] The above-mentioned method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material is characterized in that the CuCrNb powder in step one is composed of the following components in percentage by mass: Cr 0.16%~8.97%, Nb 0.15%~7.29%, and the molar ratio of Cr to Nb is 2~2.2:1, and the balance is copper.

[0009] The above-mentioned method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material is characterized in that the mass of the LaB6 powder in step one accounts for 0.1%~3% of the mass of the CuCrNb composite powder coated with LaB6, and the particle size of the LaB6 powder is less than 1μm.

[0010] The above-mentioned method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material is characterized in that the ball-to-material ratio of the ball milling mixing in step 1 is 2~5:1, the ball milling speed is 100rpm~300rpm, and the ball milling time is 5h~10h. The process parameters of the ball milling mixing ensure the mixing degree of LaB6 powder and CuCrNb powder without destroying the composition and size of the two powders. By controlling the ball milling mixing process, the composition and size of LaB6 powder and CuCrNb powder are avoided from being destroyed, and a uniform composite powder is obtained.

[0011] The above-mentioned method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material is characterized in that the additive manufacturing described in step 2 adopts a laser powder bed fusion method or a directed energy deposition method.

[0012] The above-mentioned method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material is characterized in that the temperature of the aging heat treatment in step three is 400°C~500°C, and the aging time is 0.5h~5h. By controlling the temperature and time of the aging heat treatment, a large amount of internal stress caused by rapid cooling in additive manufacturing can be eliminated, thereby effectively avoiding the low plasticity caused by stress concentration when the composite material is in service; at the same time, a small amount of solid-solution elements dissolved in the copper matrix continue to precipitate in the nanophase, enhancing the strength of the composite material, and the reduction of solid-solution elements in the copper matrix is ​​conducive to improving the thermal conductivity of the composite material.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The present invention selects CuCrNb powder as the matrix raw material, and utilizes the high melting point intermetallic compound Cr2Nb itself to strengthen the copper matrix, thereby ensuring the thermal stability of the copper-based composite material, so that it has the comprehensive properties of high strength and high conductivity. At the same time, the matrix raw material can be CuCrNb spherical alloy powder prepared by gas atomization or CuCrNb composite powder prepared by mechanical alloying, and the raw material source is wide and the practicability is high.

[0014] 2. Regarding the additive manufacturing method of laser light source, the present invention adopts mechanical ball milling to prepare composite powder, so that micron and nanometer-sized LaB6 powder is coated on the outer layer of CuCrNb powder, which overcomes the problem that the copper alloy powder, especially the spherical copper alloy powder prepared by atomization, has a large laser reflectivity, resulting in low additive manufacturing efficiency. LaB6 has good laser absorption ability and photothermal conversion performance, so the CuCrNb composite powder coated with LaB6 has high laser absorption and photothermal conversion ability, which effectively improves the absorption rate of laser in the additive manufacturing process, thereby improving the efficiency of additive manufacturing and reducing energy consumption. At the same time, the molten pool formed in the additive manufacturing process has good connectivity, reducing the porosity of the additively manufactured molded parts, thereby improving the density and comprehensive performance of the additively manufactured molded parts.

[0015] 3. Aiming at the contradictory problems that a large amount of Cr2Nb agglomerates are easily generated in CuCrNb powder with high Cr and Nb contents, which affects the mechanical properties of the composite material, and the strengthening effect is limited due to insufficient amount of Cr2Nb reinforcing phase in CuCrNb powder with low Cr and Nb contents, the present invention introduces a high melting point and high conductivity ceramic reinforcing phase LaB6 into CuCrNb powder with low Cr and Nb contents. Since LaB6 has a smaller wetting angle with liquid copper and has almost no solid solubility in the copper matrix at low temperature, under the ultra-high energy density and high cooling rate of additive manufacturing, LaB6 with a melting point greater than 2200°C is quickly dissolved and precipitated and dispersed in the copper matrix in nanometer size. At the same time, the Cr2Nb reinforcing phase generated in the CuCrNb powder is further refined in the process, thereby increasing the type and amount of nanometer-sized reinforcing phases. The two work together to precipitate, disperse and strengthen the pinning of dislocations and hinder grain boundary migration, greatly improving the thermal stability of the copper-based composite material, so that the copper-based composite material still exhibits high strength after thermal exposure and retains excellent thermal and electrical conductivity.

[0016] 4. The present invention uses LaB6 as a reinforcing phase and adopts a high-energy-density additive manufacturing method. During the process, the high-melting-point LaB6 is first rapidly precipitated in nanometer size as it cools, and then nano-Cr2Nb is rapidly precipitated, ensuring that each nano-phase is evenly dispersed and precipitated separately to avoid agglomeration, thereby increasing the number of nano-precipitated phases, thereby giving full play to the dual advantages of low-content Cr2Nb and LaB6, and improving the room temperature and high-temperature strength, thermal stability and high thermal conductivity of the copper-based composite material.

[0017] 5. The LaB6 ceramic reinforcement phase introduced into the copper-based composite material of the present invention has a higher melting point and extremely low solid solubility. Under the high-temperature service conditions of the copper-based composite material, when part of the Cr2Nb or Cr nano-reinforcement phase gradually fails, the high-melting-point LaB6 ceramic reinforcement phase can still provide a strengthening effect, thereby ensuring the thermal stability of the copper-based composite material.

[0018] 6. The present invention controls the ratio of CuCrNb powder to LaB6 powder, rationally adjusts the content ratio of Cr2Nb and LaB6 ceramic reinforcement phases, improves the synergistic enhancement of strength, plasticity, thermal stability and other effects of LaB6 and Cr2Nb on copper-based composite materials, thereby balancedly adjusting the comprehensive performance of the copper-based composite materials to meet the use requirements, and at the same time combines aging heat treatment to eliminate the internal stress of the copper-based composite materials, continues to promote the precipitation of reinforcement phase nano-Cr2Nb or Cr, and further optimizes the comprehensive performance of the copper-based composite materials.

[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a flow chart of the preparation process of the LaB6 and Cr2Nb synergistically reinforced copper-based composite material in the present invention. DETAILED DESCRIPTION

[0021] The CuCrNb powder used in Examples 1 to 6 of the present invention and Comparative Example 1 is a CuCrNb spherical alloy powder prepared by a gas atomization method or a CuCrNb composite powder prepared by a mechanical alloying method, and has a particle size of less than 50 μm; the particle size of the selected LaB6 powder is less than 1 μm.

[0022] Example 1 like Figure 1 As shown, this embodiment includes the following steps: Step 1: Place 1.5 g of LaB6 powder and 148.5 g of CuCrNb powder in a stainless steel ball mill, add stainless steel grinding balls according to a ball-to-material ratio of 3:1, and use a ball mill to mill at a speed of 200 rpm for 8 hours. The type and composition of the CuCrNb powder are shown in Table 1 A below, and a CuCrNb composite powder coated with LaB6, namely, LaB6@CuCrNb composite powder, is obtained; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 for additive manufacturing, a formed part, i.e., a formed LaB6 and Cr2Nb synergistically reinforced copper-based composite material, is obtained by laser powder bed fusion (LPBF); Step three, placing the molded part obtained in step three into a heat treatment furnace for aging heat treatment, the aging temperature is 450°C, the aging time is 2h, and an aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material is obtained.

[0023] According to the test, the thermal conductivity of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in this embodiment is 281 W / mK, and the tensile strength is 483 MPa.

[0024] Example 2 like Figure 1 As shown, this embodiment includes the following steps: Step 1: 4.5 g of LaB6 powder and 145.5 g of CuCrNb powder were placed in a stainless steel ball mill, stainless steel grinding balls were placed in a ball-to-material ratio of 5:1, and the balls were milled at a speed of 300 rpm for 5 h. The type and composition of the CuCrNb powder are shown in B of Table 1 below, and the CuCrNb composite powder coated with LaB6, i.e., LaB6@CuCrNb composite powder, was obtained; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 for additive manufacturing, a formed part, i.e., a formed LaB6 and Cr2Nb synergistically reinforced copper-based composite material, is obtained by laser powder bed fusion (LPBF); Step three, placing the molded part obtained in step three into a heat treatment furnace for aging heat treatment, the aging temperature is 500°C, the aging time is 0.5h, and an aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material is obtained.

[0025] According to the test, the thermal conductivity of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in this embodiment is 321 W / mK, and the tensile strength is 430 MPa.

[0026] Example 3 like Figure 1 As shown, this embodiment includes the following steps: Step 1: Place 0.15 g of LaB6 powder and 149.85 g of CuCrNb powder in a stainless steel ball mill, add stainless steel grinding balls according to a ball-to-material ratio of 2:1, and use a ball mill to mill at a speed of 100 rpm for 10 hours. The type and composition of the CuCrNb powder are shown in C of Table 1 below, and a CuCrNb composite powder coated with LaB6, i.e., LaB6@CuCrNb composite powder, is obtained; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 for additive manufacturing, and using directed energy deposition (DED) to obtain a molded part, i.e., a molded LaB6 and Cr2Nb synergistically reinforced copper-based composite material; Step three, placing the molded part obtained in step three into a heat treatment furnace for aging heat treatment, the aging temperature is 400°C, the aging time is 5h, and an aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material is obtained.

[0027] According to the test, the thermal conductivity of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in this embodiment is 245 W / mK, and the tensile strength is 418 MPa.

[0028] Example 4 like Figure 1 As shown, this embodiment includes the following steps: Step 1: Place 0.15 g of LaB6 powder and 149.85 g of CuCrNb powder in a stainless steel ball mill, add stainless steel grinding balls according to a ball-to-material ratio of 3:1, and use a ball mill to mill at a speed of 200 rpm for 8 hours. The type and composition of the CuCrNb powder are shown in D of Table 1 below, and a CuCrNb composite powder coated with LaB6, namely, LaB6@CuCrNb composite powder, is obtained; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 for additive manufacturing, a formed part, i.e., a formed LaB6 and Cr2Nb synergistically reinforced copper-based composite material, is obtained by laser powder bed fusion (LPBF); Step three, the molded part obtained in step three is placed in a heat treatment furnace for aging heat treatment, the aging temperature is 450°C, the aging time is 2h, and the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material is obtained.

[0029] According to the test, the thermal conductivity of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in this embodiment is 274 W / mK, and the tensile strength is 442 MPa.

[0030] Example 5 like Figure 1 As shown, this embodiment includes the following steps: Step 1: 4.5 g of LaB6 powder and 145.5 g of CuCrNb powder were placed in a stainless steel ball mill, stainless steel grinding balls were placed in a ball-to-material ratio of 5:1, and the balls were milled at a speed of 300 rpm for 5 h. The type and composition of the CuCrNb powder are shown in E of Table 1 below, and CuCrNb composite powder coated with LaB6, i.e., LaB6@CuCrNb composite powder, was obtained; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 for additive manufacturing, a formed part, i.e., a formed LaB6 and Cr2Nb synergistically reinforced copper-based composite material, is obtained by laser powder bed fusion (LPBF); Step three, placing the molded part obtained in step three into a heat treatment furnace for aging heat treatment, the aging temperature is 500°C, the aging time is 0.5h, and an aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material is obtained.

[0031] According to the test, the thermal conductivity of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in this embodiment is 308 W / mK, and the tensile strength is 419 MPa.

[0032] Example 6 like Figure 1 As shown, this embodiment includes the following steps: Step 1: Place 1.5 g of LaB6 powder and 148.5 g of CuCrNb powder in a stainless steel ball mill, add stainless steel grinding balls according to a ball-to-material ratio of 2:1, and use a ball mill to mill at a speed of 100 rpm for 10 hours. The type and composition of the CuCrNb powder are shown in F of Table 1 below, and a CuCrNb composite powder coated with LaB6, namely, LaB6@CuCrNb composite powder, is obtained; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 for additive manufacturing, and using directed energy deposition (DED) to obtain a molded part, i.e., a molded LaB6 and Cr2Nb synergistically reinforced copper-based composite material; Step three, the molded part obtained in step three is placed in a heat treatment furnace for aging heat treatment, the aging temperature is 400°C, the aging time is 5h, and an aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material is obtained.

[0033] According to the test, the thermal conductivity of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in this embodiment is 220 W / mK, and the tensile strength is 378 MPa.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 1, LaB6 powder is not added for ball milling, and CuCrNb powder is directly subjected to additive manufacturing and aging heat treatment to obtain an aged CuCrNb alloy.

[0035] According to the test, the thermal conductivity of the aged CuCrNb alloy prepared in this comparative example is 268 W / mK, and the tensile strength is 389 MPa.

[0036] Table 1

[0037] In Table 1, "Bal." indicates a margin.

[0038] By comparing Example 1 of the present invention with Comparative Example 1, it can be seen that compared with Comparative Example 1, the tensile strength of the aged LaB6 and Cr2Nb synergistically reinforced copper-based composite material prepared in Example 1 is greatly increased, and the thermal conductivity is slightly improved, indicating that the dissimilar reinforcing phases prepared by the method of the present invention can improve the mechanical properties and electrical conductivity of the copper-based composite material.

[0039] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material, characterized in that: The method comprises the following steps: Step 1: ball-milling LaB6 powder and CuCrNb powder to obtain CuCrNb composite powder coated with LaB6; Step 2: Using the LaB6-coated CuCrNb composite powder obtained in step 1 to perform additive manufacturing to obtain a molded part; Step three: performing aging heat treatment on the molded part obtained in step two to obtain a LaB6 and Cr2Nb synergistically reinforced copper-based composite material.

2. The method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material according to claim 1, characterized in that: The CuCrNb powder in step 1 is a CuCrNb spherical alloy powder prepared by a gas atomization method or a CuCrNb composite powder prepared by a mechanical alloying method, and the particle size is less than 50 μm.

3. The method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material according to claim 1, characterized in that: The CuCrNb powder in step 1 is composed of the following components in percentage by weight: Composition: Cr 0.16%~8.97%, Nb 0.15%~7.29%, and the molar ratio of Cr to Nb is 2~2.2:1, and the balance is copper.

4. The method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material according to claim 1, characterized in that: The mass of the LaB6 powder in step 1 accounts for 0.1% to 3% of the mass of the CuCrNb composite powder coated with LaB6, and the particle size of the LaB6 powder is less than 1 μm.

5. The method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material according to claim 1, characterized in that: The ball-to-material ratio of the ball-milling mixture in step 1 is 2-5:1, the ball-milling speed is 100 rpm-300 rpm, and the ball-milling time is 5 h-10 h.

6. The method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material according to claim 1, characterized in that: The additive manufacturing described in step 2 adopts a laser powder bed fusion method or a directed energy deposition method.

7. The method for preparing a LaB6 and Cr2Nb synergistically reinforced copper-based composite material according to claim 1, characterized in that: The temperature of the aging heat treatment in step 3 is 400°C to 500°C, and the aging time is 0.5h to 5h.

Citation Information

Cited By

  • Preparation method of multi-element in-situ co-coated core-shell powder for additive manufacturing

    CN120619362A

  • Preparation method of micron LaB6 copper-based composite material, material and laser additive manufacturing method of micron LaB6 copper-based composite material

    CN121406934A